Food Waste Management: A McDonald’s Consumer Perspective - Fouten, Luke (The IIE, 2022)
Food waste has been highlighted globally as being a significant problem and phenomenon. In South Africa a third of the food produced is not consumed and ends up being disposed. This approximately equates to 10 million tonnes of food being waste in South Africa out of the 31 million tonnes produced (WWF, 2017). The financial burden due to this food loss comes to a loss of R61.5 billion. The energy wasted annually due to producing food that is wasted is said to have been able to power the City of Johannesburg for up to 16 weeks (WWF, 2017). Successfully reducing and cutting out food waste allows the country to change the realities of many food insecure portions of the population (WWF, 2017). This research study took the form of an interpretivist, qualitative research design. The research instrument undertaken was that of a digital questionnaire distributed online. The sample included South African McDonald’s consumers aged between 18 – 60 years old. 3 themes were generated from the findings and data collected which include (1) Lack of awareness and knowledge on food waste management, (2) Food waste generated by consumers, (3) Food waste management methods implemented by consumer households.
Keywords: Fast food; Households; Consumer behaviour; Meaningful brands; Food scarcity